The effectiveness of diphenyltin (IV) and triphenyltin (IV) alkylphenyldithiocarbamate compounds as insecticide against aedes aegypti LINN. (Diptera: Culicidae) in laboratory - Normah Awang,; Rosalina Kasim,; Hidayatulfathi Othman,; Nurul Farahana Kamaludin, (penerbit ukm, 2014)
The development of using insecticide of organotin(IV) compound against Aedes aegypti mosquitoes have been explored and test the effectiveness of compound to prevent resistance insecticide. The aim of this research was to examine the insecticidal effect which is larvisidal and adulticidal effect two series of diphenyltin(IV) and triphenyltin(IV) alkylphenyldithiocarbamate compounds against Ae. aegypti in laboratory. Four compounds which diphenyltin(IV) ethylphenylditiocarbamate (DFEF), triphenyltin(IV) ethylphenylditiocarbamate (TFEF), diphenyltin(IV) butylphenylditiocarbamate (DFBF) and triphenyltin(IV) butylphenylditiocarbamate(DFBF) were carried out larvicidal bioassay testing against third instar larvae of Aedes aegypti. Based on activity of larvicidal testing, further study was continued to compound WHO showed the best activity larvicidal to test adulticide effect against female mosquito adults of Aedes aegypti. The results showed that TFEF compound showed the best larvicidal effect with LC50 and LC90 values of 0.082 ppm and 0.184 ppm, respectively. Therefore, TFBF compound showed a good larvicide effect with LC50 and LC90 values of 0.108 ppm and 0.273 ppm respectively. However, both of two compounds DFEF and DFBF were not a good of larvicide effect. Based on adultisial testing, TFEF compound not showed good activity of adulticidal effect with high LC50 and LC90 values which is 31,556.03 ppm and 98,427.05 ppm respectively. TFEF compound not show the good adulticide effect but it has potential to develop as larvicide. In conclusion, further study was needed to elucidate and ensure this compound will be used safely as larvicide.